Seasonal variation of fatty acid compositions in freshwater crayfish (Pontastacus leptodactylus Eschscholtz, 1823) - Gülşen Uzun Gören (Journal of Freshwater Ecology)
This study aims to determine the fatty acid composition of Pontastacus leptodactylus Eschscholtz, 1823 crayfish living in Cernek Lake in Bafra Fish Lakes in four seasons. The study was carried out over a period of one year. The crayfish used in the study were randomly sampled from their natural habitat at legal catch sizes. It was found that there was no difference in saturated fatty acid (SFA) concentrations among autumn/summer and spring/winter seasons, but there was a difference (p < 0.05) among autumn/winter and spring/summer seasons. It was found that there was a difference (p < 0.05) between the concentrations of monounsaturated fatty acids (⅀MUFA) in the spring and summer seasons. While the concentrations of polyunsaturated fatty acids (⅀PUFA) showed similar characteristics in the summer and autumn seasons, it was found that the concentrations were different in the other seasons (p < 0.05). It was also found that eicosapentaenoic acid (EPA) concentrations were lowest in spring and highest in summer, and the annual mean was 13.16 ± 1.10. Docosahexaenoic acid (DHA) concentrations were highest in winter and the annual mean was 6.79 ± 0.33. EPA+DHA concentrations were highest in the summer season and the annual mean was 19.96 ± 1.26. Omega-3 (ω-3) concentrations were highest in spring and lowest in autumn. In addition, the average annual ⅀Omega 3 (ω-3) concentration was 25.05 ± 4.62. ⅀Omega 6 (ω-6) concentrations were highest in winter and lowest in summer, and the annual general average was 18.60 ± 2.12. The annual average of ⅀ω-3/⅀ω-6 ratios was 1.36 ± 0.33. Based on the results of this study, these crayfish are an important source of (ω-3) fatty acids. This investigation will have a beneficial impact on the local market and potential aquaculture activities.